2014
DOI: 10.1111/jocn.12602
|View full text |Cite
|
Sign up to set email alerts
|

The impact of death and dying on nursing students: an explanatory model

Abstract: Adequate training of this kind would help to ensure that future nurses offer high-quality care to patients and their families, minimising the impact of death and preventing emotional fatigue.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
73
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(80 citation statements)
references
References 64 publications
1
73
0
2
Order By: Relevance
“…It is therefore important for nursing students to become aware of their own feelings and to receive the time and opportunity to reflect on these feelings during their education. This is supported by Edo-Gual et al (2014), who reported that nursing students require training in end-of-life care, with special focus on training to manage their emotions. Previous research has demonstrated that when not provided with opportunities to discuss and reflect on their impressions, students in their final year of education perceive their education regarding terminally ill patients and end-of-life care as shallow compared with the perceptions of first-year students who did receive this opportunity (Mutto et al, 2010).…”
Section: Discussionmentioning
confidence: 69%
See 2 more Smart Citations
“…It is therefore important for nursing students to become aware of their own feelings and to receive the time and opportunity to reflect on these feelings during their education. This is supported by Edo-Gual et al (2014), who reported that nursing students require training in end-of-life care, with special focus on training to manage their emotions. Previous research has demonstrated that when not provided with opportunities to discuss and reflect on their impressions, students in their final year of education perceive their education regarding terminally ill patients and end-of-life care as shallow compared with the perceptions of first-year students who did receive this opportunity (Mutto et al, 2010).…”
Section: Discussionmentioning
confidence: 69%
“…Nursing students have also acknowledged that encounters with death can be a learning experience, which could lead to personal growth. According to Edo-Gual et al (2014), it is important to work with designing adequate training programmes regarding end-of-life care in order to ensure that future nurses, above all, offer highquality care to patients and their families, while minimising the negative impact of encountering death and thereby preventing emotional fatigue.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Proper training would help ensure that these professionals develop skills to provide quality care to patients and families, minimizing the impact of death and preventing emotional exhaustion. 7 However, the training of health professionals has superficially dealt with the issue of death, giving more emphasis on discussions of curative approaches, which diminishes the training opportunities of the graduating nurse, hindering the practice of care related to human death and dying. 8 This fact is highlighted by the few subjects taught in the undergraduate curricula of health courses that deal with this theme that are insufficient for a sensitive approach to care in face of the human needs during this phase.…”
Section: Introductionmentioning
confidence: 99%
“…Lack of time, work overload, or institutional support can limit the availability of nursing professionals to carry out adequately the mentor function. (9,10) In some cases, deficiencies exist in teaching methodology, lack of clear evaluation criteria, (11) or inadequate communication between professors and mentors, which are obstacles that can have negative impact on student evaluations during the clinical practices. (12) Further, nursing professionals must have skills, like experience, enthusiasm, positive attitude, (5,13) commitment, and level of implication (6,9) necessary to achieve effective learning.…”
Section: Introductionmentioning
confidence: 99%